A competencies framework of visual impairments for enabling shared understanding in design - Reyes Cruz, Aurea Gisela (2023)
Existing work in Human Computer Interaction and accessibility research has long sought to investigate the experiences of people with visual impairments in order to address their needs through technology design and integrate their participation into different stages of the design process. Yet challenges remain regarding how disabilities are framed in technology design and the extent of involvement of disabled people within it. Furthermore, accessibility is often considered a specialised job and misunderstandings or assumptions about visually impaired people’s experiences and needs occur outside dedicated fields. This thesis presents an ethnomethodology-informed design critique for supporting awareness and shared understanding of visual impairments and accessibility that centres on their experiences, abilities, and participation in early-stage design. This work is rooted in an in-depth empirical investigation of the interactional competencies that people with visual impairments exhibit through their use of technology, which informs and shapes the concept of a Competencies Framework of Visual Impairments. Although past research has established stances for considering the individual abilities of disabled people and other social and relational factors in technology design, by drawing on ethnomethodology and its interest in situated competence this thesis employs an interactional perspective to investigate the practical accomplishments of visually impaired people. Thus, this thesis frames visual impairments in terms of competencies to be considered in the design process, rather than a deficiency or problem to be fixed through technology. Accordingly, this work favours supporting awareness and reflection rather than the design of particular solutions, which are also strongly needed for advancing accessible design at large. This PhD thesis comprises two main empirical studies branched into three different investigations. The first and second investigations are based on a four-month ethnographic study with visually impaired participants examining their everyday technology practices. The third investigation comprises the design and implementation of a workshop study developed to include people with and without visual impairments in collaborative reflections about technology and accessibility. As such, each investigation informed the ones that followed, revisiting and refining concepts and design materials throughout the thesis. Although ethnomethodology is the overarching approach running through this PhD project, each investigation has a different focus of enquiry: • The first is focused on analysing participants’ technology practices and unearthing the interactional competencies enabling them. • The second is focused on analysing technology demonstrations, which were a pervasive phenomenon recorded during fieldwork, and the work of demonstrating as exhibited by visually impaired participants. • Lastly, the third investigation defines a workshop approach employing video demonstrations and a deck of reflective design cards as building blocks for enabling shared understanding among people with and without visual impairments from different technology backgrounds; that is, users, technologists, designers, and researchers. Overall, this thesis makes several contributions to audiences within and outside academia, such as the detailed accounts of some of the main technology practices of people with visual impairments and the methodological analysis of demonstrations in empirical Human Computer Interaction and accessibility research. Moreover, the main contribution lies in the conceptualisation of a Competencies Framework of Visual Impairments from the empirical analysis of interactional competencies and their practical exhibition through demonstrations, as well as the creation and use of a deck of cards that encapsulates the competencies and external elements involved in the everyday interactional accomplishments of people with visual impairments. All these contributions are lastly brought together in the implementation of the workshop approach that enabled participants to interact with and learn from each other. Thus, this thesis builds upon and advances contemporary strands of work in Human Computer Interaction that call for re-orienting how visual impairments and, overall, disabilities are framed in technology design, and ultimately for re-shaping the design practice itself.